Prognostic value of PNN in prostate cancer and its correlation with therapeutic significance - Wang, Ruisong; Qin, Ziyi; Luo, Huiling; Pan, Meisen; Liu, Mingyao; Yang, Pinhong; Shi, Tieliu (Frontiers in Genetics, 2022)
Prostate cancer (Pca) is the most common malignancy. New biomarkers are in demand to facilitate the management. The role of the pinin protein (encoded by PNNgene) in PCa has not been thoroughly explored yet. Using The Cancer Genome Atlas (TCGA-PCa) dataset validated with Gene Expression Omnibus (GEO) and protein expression data retrieved from the Human Protein Atlas, the prognostic and diagnostic values of PNN were studied. Highly co-expressed genes with PNN (HCEG) were constructed for pathway enrichment analysis and drug prediction. A prognostic signature based on methylation status using HCEG was constructed. Gene set enrichment analysis (GSEA) and the TISIDB database were utilised to analyse the associations between PNN and tumour-infiltrating immune cells. The upregulated PNN expression in PCa at both transcription and protein levels suggests its potential as an independent prognostic factor of PCa. Analyses of the PNN's co-expression network indicated that PNN plays a role in RNA splicing and spliceosomes. The prognostic methylation signature demonstrated good performance for progression-free survival. Finally, our results showed that the PNN gene was involved in splicing-related pathways in PCa and identified as a potential biomarker for PCa.